Procedures for Developing Inquiry-Flipped Classroom Models to Improve Argumentation Skills - Yultari Ramadani; Sahiska Prahati Erly; Ida Rosyida (STAI Hubbulwathan Duri, 2023)
This research is research on the development of a learning model procedure that refers to the research developed by Lee J.L and Jang. The research type is F2-O1+O2-S1+S5+S6-A3. The resulting product is a flow of inquiry learning model-flipped classroom. The results of validation by experts on conceptual and procedural practitioners state that the product is feasible to be tested. The results of the small group trial showed that the inquiry-flipped classroom flow model was effective for use in the learning process. From the results of the study, it can be concluded that the flow of the inquiry-flipped classroom model has gone through the development stage and received a very good response from educators. The flow of the inquiry-flipped classroom model can be used in helping the learning process to improve the ability to argue on factors that can affect the reaction rate, which is characterized by making it easier for students to form initial concepts, saving time so that there is room for argument, increasing student participation.